Modernism and hegemony : a materialist critique of aesthetic agencies - Larsen, Neil.; Concha, Jaime (Minneapolis : University of Minnesota Press, 1990)
A critique of high modernism from a newly formulated Marxist perspective, achieved through analyses of texts by Marx and Adorno, Manet's paintings, and the works of several Latin American writers. Annotation copyrighted by Book News, Inc., Portland, OR.
Foreword: From the Modernism of Adorno to the Contemporaneity of Marx; Introduction; 1. From Adorno to Marx: De-Aestheticizing the Modern; 2. Modernism, Manet, and the Maximilian: Executing Negation; 3. Juan Rulfo: Modernism as Cultural Agency; 4. Modernism as Cultura Brasileira: Eating the "Torn Halves"; Notes; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Modernism (Art); Ideology; Aesthetics, Modern -- 20th century; Aesthetics, Modern; Modernism (Art) -- Controversial literature; Modernisme (Art) -- Ouvrages de controverse; Idéologie.; Esthétique -- 20e siècle.; Modernisme (Art); ideology; PHILOSOPHY -- Aesthetics; PHILOSOPHY -- General; Aesthetics, Modern; Ideology; Modernism (Art); 1900-1999; Controversial literature